PERITONEAL LAVAGE - ITS ROLE IN IMPROVING DIAGNOSTIC ACCURACY OF INTRA-ABDOMINAL TRAUMA - Mufti, Tariq; Khan, Khalid; Malik, Sajjad A.; Mushtaq, Tahir (Journal of Ayub Medical College Abbottabad, 1993)
Out of forty cases admitted with abdominal injuries eleven were subjected to diagnostic peritoneal lavage due to inconclusive clinical findings, ten out of eleven cases gave true positive or negative findings giving high index of reliability, no untoward effects of the procedure were recorded